2018
DOI: 10.3329/bpj.v21i2.37922
|View full text |Cite
|
Sign up to set email alerts
|

In vitro Effect of Withania somnifera, Mucuna pruriens and Pausinystalia johimbe on Hepatic Cytochrome P450 in Rat

Abstract: The effect of Withania somnifera, Mucuna pruriens and Pausinystalia johimbe extracts on hepatic cytochrome P450 enzyme CYP3A4 activities was studied using rat liver microsomes. CYP3A4-dependent testosterone 6β-hydroxylation activities were determined by ELISA. In the study, rats were treated with W. somnifera (0.5 g/kg/day), M. pruriens (0.5 g/kg/day) and P. johimbe (0.25 g/kg/day) extracts for 20 days. It was found that W. somnifera, M. pruriens and P. johimbe extracts showed potent to moderate inhibitory eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Proposed mechanisms underlying those events involve: 1) interactions between adaptogen and cytochrome 450 isoenzymes responsible for antidepressant metabolism and 2) the addition of side effects of both substances. The first mechanism is related to the suggested inhibitory effect of Withania somnifera extracts on CYP3A4 and CYP2D6 ( Brinker, 2010 ; Sultana and Sultan, 2018 ). This results in an increase in the concentration and side effects of antidepressants metabolized by those cytochromes, particularly escitalopram (myalgia of intensity >5 according to the numeric rating scale (NRS), epigastric pain, nausea, vomiting, restless legs syndrome, and severe non-productive cough), paroxetine (generalized myalgia (NRS = 4–5), ophthalmalgia, and ocular hypertension), and reboxetine (testicle pain, ejaculatory dysfunctions, and pain during ejaculation).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Proposed mechanisms underlying those events involve: 1) interactions between adaptogen and cytochrome 450 isoenzymes responsible for antidepressant metabolism and 2) the addition of side effects of both substances. The first mechanism is related to the suggested inhibitory effect of Withania somnifera extracts on CYP3A4 and CYP2D6 ( Brinker, 2010 ; Sultana and Sultan, 2018 ). This results in an increase in the concentration and side effects of antidepressants metabolized by those cytochromes, particularly escitalopram (myalgia of intensity >5 according to the numeric rating scale (NRS), epigastric pain, nausea, vomiting, restless legs syndrome, and severe non-productive cough), paroxetine (generalized myalgia (NRS = 4–5), ophthalmalgia, and ocular hypertension), and reboxetine (testicle pain, ejaculatory dysfunctions, and pain during ejaculation).…”
Section: Discussionmentioning
confidence: 99%
“…However, there are conflicting results concerning the nature of those interactions. In vitro studies reported that Withania somnifera extracts may inhibit ( Sultana and Sultan, 2018 ), induce ( Kumar et al, 2021a ), or reveal no significant impact on CYP3A4 ( Savai et al, 2013 , Savai et al, 2015 ). Further studies are required to understand the associations between CYP isoenzymes and Withania somnifera extracts, as well as the clinical relevance of these findings.…”
Section: Discussionmentioning
confidence: 99%